The European Union and China's Belt and Road : impact, engagement and competition - Ntousas, Vassilis; Minas, Stephen (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book explores key elements of EU engagement with the Belt Road Initiative (BRI), drawing on the expertise of leading practitioners and scholars of EU-China relations. Under the theme of discerning the BRI and its nexus with the EU, chapters examine the nature of the BRI as China's approach to global governance and consider how BRI intersects with the EU as a very different regional integration project. Under the theme of BRI factors in EU law and policy, chapters examine the BRI as a factor in specific domains of EU law and policy, including investment, finance, the environment and the COVID-19 pandemic, and consider EU responses. Under the theme of EU Member State experiences, chapters present a series of case studies of individual Member States, their engagement with the BRI and ongoing policy debates. This book will be of key interest to scholars and students of International Relations, EU external relations, Chinese public policy and foreign relations, European studies and security studies as well as policymakers dealing with China in EU and Member State institutions"--
Foreword / by Thanos Dokos -- Introduction: The Belt and Road and EU international relations policy and law / Vassilis Ntousas and Stephen Minas -- The Belt and Road Initiative as China's approach to global governance : implications for China-EU relations and economic cooperation / Yun Zhao and Hui Chen -- EU-China diplomacy and the Belt and Road Initiative / Jing Men -- The BRI kaleidoscope : European legal pluralism and BRI soft law / Francis Snyder -- The Belt and Road in the single market : towards an EU legal infrastructure to address the regulatory implications / Steven Blockmans and Weinian Hu -- Sino-European financial linkages underpinning BRI projects in Europe / Jens Bastian -- The Belt and Road Initiative and state-owned enterprises : is it time for reform of the EU merger control? / Alexandr Svetlicinii -- EU-China cooperation on promoting sustainable development under the Belt and Road Initiative : consensus built on divergence / Xueji Su -- COVID-19 and EU-China relations / Mario Esteban and Ugo Armanini -- France, China and the BRI : the challenge of conditional engagement / Françoise Nicolas -- Between commerce and geopolitics : is there a German China strategy? / Stefan Mair and Ferdinand Schaff -- Greece between crisis, opportunity and risk as a key BRI node / Dimitris Kokoromytis and Angelos Chryssogelos -- Italy's embrace of BRI and the role of internal political dynamics / Alessia Amighini -- China and the Belt and Road Initiative in Europe : the case of Portugal / Laura-Ferreira Pereira and Paulo Duarte -- Conclusion: The EU's Belt and Road challenge : coherence, consolidation and connectivity / Vassilis Ntousas and Stephen Minas.
Keywords: European Union; Yi dai yi lu (Initiative : China); European Union countries -- Foreign economic relations -- China; China -- Foreign economic relations -- European Union countries; European Union countries -- Economic policy; China -- Economic policy